2017
DOI: 10.1016/j.ejphar.2016.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological studies on the NOP and opioid receptor agonist PWT2-[Dmt1]N/OFQ(1-13)

Abstract: An innovative chemical strategy named peptide welding technology (PWT) has been developed for the facile synthesis of tetrabranched peptides. [Dmt1]N/OFQ(1-13)-NH2 acts as a universal agonist for nociceptin/orphanin FQ (N/OFQ) and classical opioid receptors. The present study investigated the pharmacological profile of the PWT derivative of [Dmt1]N/OFQ(1-13)NH2 (PWT2-[Dmt1]) in several assays in vitro and in vivo after spinal administration in monkeys subjected to the tail withdrawal assay. PWT2-[Dmt1] mimicke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 38 publications
3
15
1
Order By: Relevance
“…It has been shown that ROS activates GRP78/PERK signal transduction, which induces apoptosis via ER stress in cervical cancer cells [39]. This finding is consistent with a recent report that luteolin, a common dietary flavonoid, induces the ER stress response and mitochondrial dysfunction by increasing intracellular ROS levels in glioblastoma cells [40]. Another study reported that JS-K, a glutathione S transferase (GST)-activated nitric oxide (NO) donor prodrug, promotes apoptosis by inducing ROS production in human prostate cancer cells [41].…”
Section: Discussionsupporting
confidence: 82%
“…It has been shown that ROS activates GRP78/PERK signal transduction, which induces apoptosis via ER stress in cervical cancer cells [39]. This finding is consistent with a recent report that luteolin, a common dietary flavonoid, induces the ER stress response and mitochondrial dysfunction by increasing intracellular ROS levels in glioblastoma cells [40]. Another study reported that JS-K, a glutathione S transferase (GST)-activated nitric oxide (NO) donor prodrug, promotes apoptosis by inducing ROS production in human prostate cancer cells [41].…”
Section: Discussionsupporting
confidence: 82%
“…Notably, whereas some mixed MOR-NOP receptor peptide ligands were reported in the literature as potential analgesics [ 55 , 56 , 57 , 58 ], their antinociceptive properties were described only in acute thermal nociception (tail-flick test) when injected i.t. or i.c.v.…”
Section: Discussionmentioning
confidence: 99%
“…59 Collectively, this evidence strongly suggests that mixed NOP/opioid receptor agonists may have therapeutic potential as novel analgesics. Some compounds with the above pharmacological profile have been reported in the literature including the peptides [Dmt 1 ]N/OFQ(1e13)-NH 2 60 and its tetrameric deriva- 61 DeNo (a dermorphin-N/OFQ chimeric peptide), 62 and some non-peptide compounds SR16435, SR16507, and SR14150 (reviewed by Toll and colleagues 4 ) that display variable potency and efficacy at NOP and mu receptors. Moreover, BU08028 is a buprenorphine derivative that displayed high affinity for NOP and opioid receptors.…”
Section: Nop Receptor Ligands and Painmentioning
confidence: 99%